Hubungan Caring Keluarga Terhadap Kepatuhan Diet dan Minum Obat Pada Pasien Hipertensi di Puskesmas Sungai Tabuk 1: The Relationship Between Family Caring and Compliance with Diet and Medication in Hypertension Patients at Sungai Tabuk 1 Public Health Center - Halimatus Sa’diah; Rian Taslim; Subhannur Rahman (Journal of Health, 2025)
Hypertension is a health condition characterized by elevated blood pressure, often unnoticed by the individuals affected. Due to the absence of typical symptoms, hypertension is often referred to as the "silent killer." This study aims to explore the role of family caring in supporting diet and medication adherence in hypertension patients. This study utilized a descriptive quantitative research design with a cross-sectional approach. The sample consisted of 76 respondents selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using the Chi-Square test with a significance level of p < 0.05. The results of the Chi-Square test indicate a significant relationship between family caring and diet adherence (p-value = 0.000) and between family caring and medication adherence (p-value = 0.006) in hypertension patients.